2020
DOI: 10.1007/s43032-019-00137-x
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Action in Human Oocyte Maturation and Quality: Signaling Pathways, Regulation, and Clinical Impact

Abstract: The ovarian follicle luteinizing hormone (LH) signaling molecules that regulate oocyte meiotic maturation have recently been identified. The LH signal reduces preovulatory follicle cyclic nucleotide levels which releases oocytes from the first meiotic arrest. In the ovarian follicle, the LH signal reduces cyclic nucleotide levels via the CNP/NPR2 system, the EGF/EGF receptor network, and follicle/oocyte gap junctions. In the oocyte, reduced cyclic nucleotide levels activate the maturation promoting factor (MPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 385 publications
(455 reference statements)
2
47
0
1
Order By: Relevance
“…The reduced level of Gata4 expression in Erβ null GCs may contribute to reduced GC proliferation and theca cell recruitment, which would impair the maturation of follicles to the preovulatory stage (Bennett et al, 2013;Efimenko et al, 2013;LaVoie, 2014). Additionally, NPR2 plays an important role in GCs by inducing cGMP levels, which inhibits phosphodiesterase 3A, prevents cAMP hydrolysis, and retrieves the oocytes from meiotic arrest (Arroyo et al, 2020;Potter et al, 2006;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced level of Gata4 expression in Erβ null GCs may contribute to reduced GC proliferation and theca cell recruitment, which would impair the maturation of follicles to the preovulatory stage (Bennett et al, 2013;Efimenko et al, 2013;LaVoie, 2014). Additionally, NPR2 plays an important role in GCs by inducing cGMP levels, which inhibits phosphodiesterase 3A, prevents cAMP hydrolysis, and retrieves the oocytes from meiotic arrest (Arroyo et al, 2020;Potter et al, 2006;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…GCs. It has been suggested that LH/LHCGR-induced ERK activation is regulated by ADAMTS1, a metalloprotease, which is also involved in cumulus expansion and induction of ovulation (Arroyo et al, 2020;Madan et al, 2003;Shozu et al, 2005;Yung et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of the proliferative phase of the endometrium to the implantation window is regulated by estrogens, progesterone, and possibly by other unknown factors. The LH peak is the most critical factor to promote oocyte maturation, embryonic development, and synchronous endometrial receptivity [ 16 , 17 ]. The expression of LH/hCG-R on the endometrium prompted that LH/hCG-R may serve as a signal that prompts embryo implantation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of signaling through the LHCGR cascades can cause atresia of mature oocytes in zebrafish (Migliaccio et al 2018 ; Santangeli et al 2016 ) and anovulation in mouse and human (Arroyo et al 2020 ). For instance, increased DNA demethylation of LHCGR is observed in DHEA-induced PCOS mouse model (Zhu et al 2010 ) and human granulosa cells of women with PCOS (Sagvekar et al 2019 ).…”
Section: Adverse Outcome Pathways As They Relate To Key Processes Inmentioning
confidence: 99%